2013
DOI: 10.3389/fpls.2013.00046
|View full text |Cite
|
Sign up to set email alerts
|

The Reference Genome of the Halophytic Plant Eutrema salsugineum

Abstract: Halophytes are plants that can naturally tolerate high concentrations of salt in the soil, and their tolerance to salt stress may occur through various evolutionary and molecular mechanisms. Eutrema salsugineum is a halophytic species in the Brassicaceae that can naturally tolerate multiple types of abiotic stresses that typically limit crop productivity, including extreme salinity and cold. It has been widely used as a laboratorial model for stress biology research in plants. Here, we present the reference ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
223
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(229 citation statements)
references
References 72 publications
4
223
0
2
Order By: Relevance
“…1a). Complete or partial genome sequences are available for a number of other Brassicaceae species 6,[9][10][11][12][13][14] , including Aethionema arabicum 11 in the earliest diverging lineage of Brassicaceae (Fig. 1a).…”
mentioning
confidence: 99%
“…1a). Complete or partial genome sequences are available for a number of other Brassicaceae species 6,[9][10][11][12][13][14] , including Aethionema arabicum 11 in the earliest diverging lineage of Brassicaceae (Fig. 1a).…”
mentioning
confidence: 99%
“…The T. hassleriana genome is relatively small (;290 Mb: 2n = 20) and within the range of sequenced Brassicaceae species: Schrenkiella parvula (formerly Thellungiella parvula), 140 Mb (Dassanayake et al, 2011); A. thaliana, 157 Mb (Bennett et al, 2003); Arabidopsis lyrata, 207 Mb (Hu et al, 2011); Capsella rubella, 210 Mb (Slotte et al, 2013); Aethionema arabicum, 240 Mb (Haudry et al, 2013); Sisimbrium irio, 262 Mb (Haudry et al, 2013); Eutrema salsugineum (formerly Thelungiella salsuginea), 314 Mb (Wu et al, 2012;Yang et al, 2013); Leavenworthia alabamica, 316 Mb (Haudry et al, 2013); and Brassica rapa 485 Mb . To generate a high-quality draft genome assembly, we used both sequenced paired-end libraries and constructed a Bacterial Artificial Chromosome (BAC) based whole-genome profiling (WGP) physical map.…”
Section: Genome Sequencing and Integration With Physical Mapmentioning
confidence: 99%
“…Because the divergence of these angiosperm families occurred in the Paleogene and the divergence of their higher level taxonomies all occurred in the Cretaceous ( Fig. 1; Lavin et al, 2005;Stefanovic et al, 2009;D'Hont et al, 2012;Zhang et al, 2012;Peng et al, 2013;Yang et al, 2013;Kim et al, 2014;Wang et al, 2014;Zeng et al, 2014), the observed intensive expansion of NBS genes in angiosperms more likely coincided with the CretaceousPaleogene (K-P) boundary (;66 MYA). This finding suggests that different lineages of angiosperms either underwent a process to reinforce resistance or experienced increased selective pressure from environmental pathogens during this period.…”
Section: Differential Expansion During Angiosperm Evolution Shaped Tnmentioning
confidence: 99%
“…The Solanaceae nTNL genes formed 55 monophyletic lineages with nTNL genes from S. indicum (two RNL lineages The phylogenetic relationship was constructed according to the APG III system (Bremer et al, 2009). The divergence times at different nodes of angiosperms were combined from previous studies (Lavin et al, 2005;Stefanovic et al, 2009;D'Hont et al, 2012;Zhang et al, 2012;Peng et al, 2013;Yang et al, 2013;Kim et al, 2014;Wang et al, 2014;Zeng et al, 2014). The total number of NBS genes and their classification in each species are shown.…”
Section: Phylogenetic Analysis Of Nbs Genes In Major Angiosperm Cladesmentioning
confidence: 99%